Myrobalan Fruit Extracts Modulate Immunobiochemical Pathways In Vitro - Stefanie Hofer; Marcel Jenny; Angela Klein; Kathrin Becker; Lucia Parráková; Florian Überall; Markus Ganzera; Dietmar Fuchs; Hubert Hackl; Pablo Monfort-Lanzas; Johanna M. Gostner (Antioxidants)
Myrobalan fruits are important ingredients of traditional remedies, such as the Ayurvedic formulation Triphala or the Tibetan formulation Bras bu 3. Myrobalan-containing remedies are described to have positive effects on metabolism, the cardiovascular system, and the immune system. The chemical composition of botanical mixtures can be very complex, and it is often impossible to identify individual compounds as specific active ingredients, which suggests a multi-target mode of action. In this in vitro study, the effect of myrobalan extracts in human cell models was investigated to gain more information about the molecular mechanism of action and to find possible synergistic effects. Direct and indirect antioxidant effects were investigated, and the activation of immunobiochemical metabolic pathways involved in the cellular immune response was examined in cell lines treated with extracts of the fruits of Phyllanthus emblica, Terminalia chebula and Terminalia bellirica, as well as a combination of them. In particular, a synergistic effect on the activation of the endogenous antioxidant defence system was observed with the combined treatment of the three fruit extracts. An integrated transcriptome analysis of cells treated with a combination of fruit extracts confirmed an effect on immune pathways, oxidative stress, and detoxification processes. This study shows the modulation of various signalling pathways and cellular processes that may be part of the multi-target mechanism of individual and combined myrobalan fruit extracts. Although the results are limited to in vitro data, they contribute to a better understanding of how botanical mixtures work and provide hypotheses for further research.